Dysmorphic and illness anxiety‐related unwanted intrusive thoughts in individuals with obsessive–compulsive disorder. (6th July 2021) - Pascual‐Vera, Belén; Belloch, Amparo
Abstract: Background/Objective: Unwanted intrusive thoughts (UITs) are considered normal variants of the obsessions found in obsessive–compulsive disorder (OCD). Similarly, intrusive and persistent preoccupations about appearance defects in body dysmorphic disorder (BDD) and images and thoughts about illness in illness anxiety disorder (IAD) are abnormal variants of the thoughts and concerns about appearance and health found in non‐clinical individuals. This study examines whether patients with OCD have frequent and distressing UITs with contents related to BDD and IAD, in addition to OCD‐related UITs. Method: Thirty‐nine participants with OCD ( M age  = 32.45, standard deviation [ SD ] = 11.57; 63% men) completed the Questionnaire of Unpleasant Intrusive Thoughts (QUIT), designed to assess obsessional, dysmorphic and illness anxiety UITs and their associated functional consequences (emotions, appraisals, and neutralizing or control strategies). Results: Up to 71% of the individuals with OCD experienced the three UIT modalities. As expected, OCD‐related UITs were the most frequent, although were no differences among the three UIT contents in terms of the disturbance they caused. The OCD intrusions were the most interfering, egodystonic and dysfunctionally appraised, and they instigated more neutralizing behaviours. Nonetheless, all UITs instigate the need to do something to alleviate the discomfort caused by their intrusion and attempts to suppress them. Conclusion: UITs with different contents not always related to typical obsessive themes are a common experience in patients with OCD. These UITs could have detrimental consequences for the course of the disorder itself, and they should be adequately addressed in both the assessment and treatment of these patients.